Evolution of Inclusive Education: A Bibliometric Study of Scopus Data - Nazar, Lailatun; Nursalim, Mochamad; Purwoko, Budi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This research examines the shortcomings of prior studies on global inclusive education trends and patterns. The main objective is to explore and visualize scientific publications on Inclusive Education for Children, as recorded in the Scopus database from 2020 to 2024, using a bibliometric approach. The methodology used is descriptive quantitative analysis through bibliometric techniques. Data were collected by conducting a literature search using the keywords